The use of on-line analytical processing approach in developing host-parasite database system / Nur Imtiazah Bt. Shuhaimi - Nur Imtiazah, Shuhaimi (2013)

(untitled)
Biodiversity is a very broad area to explore. The developments of research have resulted in increasing the number of biodiversity data in various formats. The ability of a database in dealing with biodiversity data is essential for the effective management and information dissemination process. The capabilities of a database system rely on the formula or approaches used in operating the system. The development of On-Line Analytical Processing (OLAP) technology from time to time expands the use of this approach which previously was dominated by the business field. The effectiveness of structuring data into cube form technique allows data modeling and analysis in multidimensional view has drawn the attention of researchers from a variety of other fields and to adopt this method in producing a more conducive database system. The efficiency of online analysis as well as information retrieval which can be manipulated by the user in order to get the required information is seen as one of the factors making OLAP approach very useful in building a database, particularly in biology. A few existing biological databases that used the OLAP approach have been successful in helping researchers to manage data as well as perform relevant analysis, for instance in medical data management, gene expression and molecular sequence analysis. In this study we used OLAP in developing a host-parasite database. This thesis describes the process of parasite-host data collection, data digitization and data cleaning, followed by the construction of relational database system using online analytical processing approach. This system is named as Parasite Information Network System (PINS). PINS PARASITE INFORMATION NETWORK SYSTEM (PINS) __________________________________________________________________________________________________________ iv is designed and developed with the intention to help researchers manage data in order to preserve valuable biodiversity information by documenting the data into database storage structure. PINS is also aimed to assists researchers and students to obtain data about parasites and hosts taxonomy, biology, geography or publication of data resources information provided and use them in their studies.